ANALISIS PERKEMBANGAN PESERTA DIDIK KELAS X DALAM PROSES ADAPTASI PEMBELAJARAN DI SMA - Najin Fadila Foresta; Nayla Zalfa Destiasha; Riska Cahya Arum Sari; Surayanah (STKIP Subang, 2026)
This study was motivated by the adaptation process of 10th-grade high school students facing academic, social, and emotional changes, as well as shifts in learning motivation, after entering high school. The study aims to analyze the development of 10th-grade students in the learning adaptation process at high school based on cognitive, social, and emotional aspects, as well as motivation and future planning. The study employed a descriptive qualitative approach, with the research subjects consisting of one homeroom teacher and four 10th-grade students from Class 3 at SMAK Diponegoro. Data collection techniques included observation, interviews, and documentation. The results indicate that students experienced changes in their thinking patterns, demands for independent learning, and their ability to adapt to a new social environment. In social and emotional aspects, students demonstrated positive development through increased courage to interact, collaborate, and express opinions, although there were still obstacles in the form of low self-confidence and difficulty understanding more complex learning materials. Additionally, students’ learning motivation was influenced by support from parents, teachers, peers, and organizational experiences that helped students plan their futures more thoroughly.